STUDI KOMPARASI METODE PERCENTAGE DEPTH DOSE (PDD) DAN TISSUE PHANTOM RATIO (TPR) UNTUK MENENTUKAN INDEK KUALITAS BERKAS ENERGI 6 MV DAN 10 MV PADA PESAWAT LINAC - Laksono, Muharam Budi; Wardaya, Susila; Budi, Wahyu Setia; Hidayanto, Eko (BERKALA FISIKA, 2015)
Patient dose in the linac determined with source surface distance (SSD) technique using percentage depth dose (PDD) method and source axis distance (SAD) technique using tissue phantom ratio (TPR) method. Beam quality index is the concept of beam penetration in the water which can be quantized so get a measurable constant. In medical accelerator determined index beam quality    using TPR20,10 to do with counting of PDD20,10 or PDD(10)Research has been carried out by comparing the method PDD and TPR to determine index beam quality of  photon energy 6 MV and 10 MV on the linac. Measurements performed on the PDD method SSD 100 cm and TPR on the SAD 100 cm  with standard field 10 cm x 10 cm. PDD and percent TPR pattern is similar to the built-up area, after dmax will be different. The results of  index beam quality TPR20,10 photon energy 6 MV with a relative measurement 0.660416413 and absolute measurement 0.681884058 at 10 MV photon energies obtained relative measurement 0.73752495 and absolute measurement 0.72896543. Calculation TPR20,10 to PDD20,10 and TPR20,10 for PDD (10) of the relative and absolute measurement of the photon energy 6 MV and 10 MV obtained small deviations of less than 1%. Keywords: PDD, TPR, photon and index beam quality.